Strategi Perpustakaan Fisip Universitas Islam Negeri Bandung dalam Meningkatkan Minat Baca Mahasiswa Melalui Analisis SWOT - Nuraini Safitri; Rifka Arifatul Istiana; Rosyalinda (Gunung Djati Conference Series, 2023)
The library is a work unit in the form of a place in which there is management, collection, storage and arrangement in collecting library materials which are systematically used by users as a means of learning or even to obtain information, add insight and others. Formal education such as universities usually have libraries, but currently there are many libraries that are not well managed and their existence often does not receive special attention. This results in a lack of student interest in the books in the library so that student interest in reading becomes low. The purpose of this study was to determine the Library Management Strategy of Fisip UIN Sunan Gunung Djati in Increasing Student Reading Interest Through SWOT Analysis. This research method uses a descriptive method with a qualitative approach. Data collection techniques are carried out through observation, interviews and documentation. The results of this study indicate that the library management strategy in increasing reading interest is divided into two parts. First, internal factors, namely the condition of the library, work programs, library services, human resources and library facilities and infrastructure. Second, external factors, namely collection of books, collaboration between stakeholders, excellent service and student discipline